Designing the layout of terminals with dangerous goods for safer and more secure ports and hinterlands. Issue 2 (June 2020) - Hervás-Peralta, Miguel; Poveda-Reyes, Sara; Santarremigia, Francisco Enrique; Molero, Gemma Dolores
Highlights: Methodology that would help terminal managers and designers to make decisions. Designing the layout of safe, green, and cost-efficient ITDG and PITDG. The layout related to platforms is the most suitable from a global point of view. Considering safety, environmental and operational criteria in the decision process. Abstract: Containers entering and leaving ports are stored temporarily in the container storage yard. It is very common that ports storage in the same area non-dangerous products and dangerous goods with the risk that entails. This situation highlights the need to develop special inland terminals for containers with dangerous goods (ITDG) or at least a separated zone within the port for the storage of the dangerous goods (port inland terminal for dangerous goods [PITDG]), where containers with hazards can be stored without restrictions. The main objective of this paper is to contribute to the process of designing the layout of safe, green, and cost-efficient ITDG and PITDG by means of a methodology that would help terminal managers and designers to make decisions in a systematic way. An expert panel formed by 10 experts evaluated the layouts linked to straddle carriers, forklifts, reach stackers, platforms, and gantry cranes and achieved consensus following the Delphi method. The prioritisation of alternatives from different criteria or perspectives (e.g. economic, environment, safety, etc.) was analysed using the analytic hierarchy process (AHP). This method allows for consideration of safety, environmental, and operational criteria simultaneously in the decision-making process, which are otherwise difficult to consider. According to the criteria analysed, it was found that the layout related to platforms is the most suitable from a global point of view, followed by the layout related to gantry cranes. To ensure the robustness of the results, a sensitivity analysis was performed.